The impact of task-sharing on employee intentions to leave: A factor analytic investigation (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Among the best human resources practices following Peretti (2006), "the logic of HRM" encouraging and promoting loyalty,: Personalization, Adaptation, mobilization, sharing, Anticipation ". Through this research paper we took Sharing in the company as an example, trying to find a link between a logical component of HRM and for voluntary departure of employees.Our study is performed on a sample of 407 framework, working in listed companies, the data were collected using a questionnaire specially developed, the scales used to measure key variables (division of tasks perceivedintentions voluntary departure) were confirmed by factor analysis. The procedure developed in our research has led to satisfactory results and show that there is a negative correlation between the original intent of the voluntary and personal level of sharing within the company. Suggesting that work sharing with employees, as a human resources strategy, leads to lower for voluntary departure of employees.